2014
DOI: 10.4028/www.scientific.net/amm.681.218
|View full text |Cite
|
Sign up to set email alerts
|

The Study on the Cathodic Protection Effect of the ICCP Anodes with Exposed Conditions

Abstract: This paper presents the results of the effects of anodes for impressed current cathodic protection (ICCP) system on reinforced concrete. Experimental tests were carried out on reinforced concrete specimens with 3 different kinds of commercial anodes that are used for ICCP in order for comparative study. Results have shown that the type of anodes is irrelevant to the effectiveness of cathodic protection. CP current similarly flowed to the anodes regardless of anode types in seawater condition. In addition, curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Anode materials that normally used for ICCP include conductive coatings, titanium based mesh in cementitious overlay, conductive overlay with carbon fibers, flame-sprayed zinc and discrete anode systems [5]. Jeong and Jin [14] found that zinc bulk anode is suitable for SACP while Ti-ribbon anode for ICCP. ICCP anode system must have good electrical conductors, low rate of corrosion and the ability to resist high currents without forming resistive oxide layers [15].…”
Section: Anodes System Of Cathodic Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anode materials that normally used for ICCP include conductive coatings, titanium based mesh in cementitious overlay, conductive overlay with carbon fibers, flame-sprayed zinc and discrete anode systems [5]. Jeong and Jin [14] found that zinc bulk anode is suitable for SACP while Ti-ribbon anode for ICCP. ICCP anode system must have good electrical conductors, low rate of corrosion and the ability to resist high currents without forming resistive oxide layers [15].…”
Section: Anodes System Of Cathodic Protectionmentioning
confidence: 99%
“…Nevertheless, the electrical resistivity of concrete and corrosion rate of bars influenced by moisture content in concrete where the decrease of resistivity can increase moisture content up to 1 per cent [17]. The titanium rod anode is more effective to be used in freshwater while titanium mesh anode seems to be more effective to be used in atmospheric condition [14]. A thin layer of semi-conductive material combined with a mixed metal oxide-coated titanium tape anodes can solve the poor CP current distribution, acid generation at the anode-concrete interface and dryness of the anode-concrete interface for some structures [18].…”
Section: Anodes System Of Cathodic Protectionmentioning
confidence: 99%
See 1 more Smart Citation